Professional perspectives on fixed income portfolio management (Wiley-Academy, 2001)
The Fabozzi series provides the ultimate educational encyclopedia for the global debt capital markets. Each day, billions of dollars of debt securities trade around the world according to the principles clearly and comprehensively explained in this unrivaled series dedicated to the advancement of our knowledge-based profession." (Jack Malvey, Managing Director, Chief Global Fixed-Income Strategist, Lehman Brothers)